A Two‐Dimensional Zirconium Carbide by Selective Etching of Al3C3 from Nanolaminated Zr3Al3C5. (9th March 2016) - Zhou, Jie; Zha, Xianhu; Chen, Fan Y.; Ye, Qun; Eklund, Per; Du, Shiyu; Huang, Qing
Abstract: The room‐temperature synthesis of a new two‐dimensional (2D) zirconium‐containing carbide, Zr3 C2 Tz MXene is presented. In contrast to traditional preparation of MXene, the layered ternary Zr3 Al3 C5 material instead of MAX phases is used as source under hydrofluoric acid treatment. The structural, mechanical, and electronic properties of the synthesized 2D carbide are investigated, combined with first‐principles density functional calculations. A comparative study on the structrual stability of our obtained 2D Zr3 C2 Tz and Ti3 C2 Tz MXenes at elevated temperatures is performed. The obtained 2D Zr3 C2 Tz exhibits relatively better ability to maintain 2D nature and strucural integrity compared to Ti‐based Mxene. The difference in structural stability under high temperature condition is explained by a theoretical investigation on binding energy.